Correlation of Length of Linear Oligo(ethanamino) Amides with Gene Transfer and Cytotoxicity. Issue 9 (6th February 2014) - Scholz, Claudia; Kos, Petra; Leclercq, Laurent; Jin, Xiaoyun; Cottet, Hervé; Wagner, Ernst
Abstract The optimization of synthetic carriers for gene transfer remains a major challenge. Cationic polymers such as polyethylenimine (PEI) often show increasing gene transfer activity with increasing molecular weight, but this favorable effect is accompanied by an undesired increase in cytotoxicity. Moreover, the polydispersity of polymers prevents accurate determination of optimum size. Herein we describe the step‐by‐step elongation of precise linear oligo(ethanamino) amides by making use of the artificial amino acid succinoyl‐tetraethylene pentamine (Stp) for solid‐phase‐assisted synthesis. This procedure enabled us to identify the optimal oligomer Stp30‐W (8.4 kDa) with a length of 30 Stp units, with which effective gene transfer occurs in the absence of cytotoxicity. The transfection efficiency of Stp30‐W exceeded that of standard linear PEI (22 kDa) by sixfold; nevertheless, Stp30‐W exhibited tenfold lower cytotoxicity. In addition to the lower molecular weight, the succinate spacer between the oligoamine units may also contribute to the favorable biocompatibility. The cytotoxicity of the cationic polymer PEI is a major concern for use as a carrier for gene delivery, so this comparison between linear PEI and the new Stp oligomers is particularly relevant.